From four to nine styles: An update on individual differences in humor. (15th April 2019) - Heintz, Sonja; Ruch, Willibald
Abstract: Investigating individual differences in humor has become a popular topic for personality research. Three approaches to humor-related styles were proposed in the literature, namely Craik, Lampert, and Nelson's (1996) five bipolar styles of humorous conduct, Martin, Puhlik-Doris, Larsen, Gray, and Weir's (2003) four humor styles, and Ruch, Heintz, Platt, Wagner, and Proyer (2018) eight comic styles. The present study aims to determine how many styles can be empirically distinguished by comparing the Humor Styles Questionnaire (Martin et al., 2003) and the Comic Style Markers (Ruch, Heintz et al., 2018) in a sample of 570 German-speaking adults. The findings showed redundancies among three scales, namely the affiliative, self-enhancing, and aggressive humor styles and the comic styles fun, benevolent humor, and sarcasm. One humor style (self-defeating) and five comic styles (nonsense, wit, irony, satire, and cynicism) were distinguishable between the two measures. Thus, these findings suggest that at least nine styles should be distinguished. Eventually, developing a comprehensive model and valid measures of individual differences in humor in cumulative research programs is needed to understand how humor unfolds in our everyday lives and how it can be applied effectively in interventions. Highlights: Investigates the relationships between 4 humor styles and 8 comic styles Results in a list of nine distinguishable humor-related styles Redundancies among affiliative/fun, self-enhancing/benevolent, aggressive/sarcasm Guides future research (e.g., models) and applications (e.g., trainings) of humor